Życie dorosłych osób z niepełnosprawnością intelektualną – problematyczność realizacji potrzeby seksualności i niezależności w perspektywie rozwoju tożsamości - Marciniak-Madejska, Natalia (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2013)
The author emphasizes the influence of social attitudes towards an individual on his or her self-perception and also pays attention to what threatens the development of identity in people with intellectual disability. It is said that the most important thing in the process of identity formation is the fulfillment of three basic psychological needs during adulthood: the need for having positive relations with other people, the need for autonomy and the need for competence. The limited opportunities of adult women and men with intellectual disability to realize these needs are connected to attitudes towards people with intellectual disability such as over-protectiveness, compassion, focus on deficits, ignorance, segregation, control and judgments. These attitudes are generated by a set of social stereotypes, according to which a person with intellectual disability is an “ageless child”. People with intellectual disabilities are affected by a lack of autonomy, the impossibility of experiencing their own competence as well as limited social contacts as they stay under control of their closest social environment. These problems are concerned with the areas of sexuality and independent living. The author provides examples of discriminatory attitudes as well as current stereotypes and social beliefs which are an actual barrier to the psychosocial functioning of adult people with intellectual disability with respect to the realization of their sexual needs and needs for autonomy.